1981
DOI: 10.1038/clpt.1981.5
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil disposition in liver disease and intensive-care patients: Kinetics, clearance, and apparent blood flow relationships

Abstract: Verapamil kinetics have been determined in liver disease (mainly in cirrhotic patients), in intensive-care patients, and in healthy control subjects. Areas under the concentration-time curves (AUCs) after intravenous 5-mg and oral 80-mg doses were used to calculate systemic blood clearance, intrinsic blood clearance, and bioavailability of verapamil in patients and to calculate apparent hepatic blood flow. Intravenous data showed that verapamil clearance was reduced in all patients with liver disease (mean = -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…It is obligatory to comply with the GCP and GLP standards, with thorough record-keeping of the specificity, sensitivity, and precision of the methods used in the estimation of the product or its metabolites in the body fluids, and ensure that an accurate pharmacokinetic numerical and statistical evaluation of the data is made. The pharmacokinetic parameters for verapamil, determined in this studyfor a new retard tablet formulation of the drug, are in reasonable agreement with the data obtained earlier (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The use of k for the extrapolation of AUC po ' as AUC po n-ee=Cik, overestimates AUC po n-f rom the flip-flop phenomenon of absorption (k~and the terminal phase of elimination (~) inversion of constants: k a <A 2 • Usage of A 2 , for the intravenous experiment, for the extrapolation of AUC po ' as AUC po n_~=Cn/ A 2 , underestimates AUC po n-~because absorption is not terminated at tn=24 h after p.o.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…It is obligatory to comply with the GCP and GLP standards, with thorough record-keeping of the specificity, sensitivity, and precision of the methods used in the estimation of the product or its metabolites in the body fluids, and ensure that an accurate pharmacokinetic numerical and statistical evaluation of the data is made. The pharmacokinetic parameters for verapamil, determined in this studyfor a new retard tablet formulation of the drug, are in reasonable agreement with the data obtained earlier (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The use of k for the extrapolation of AUC po ' as AUC po n-ee=Cik, overestimates AUC po n-f rom the flip-flop phenomenon of absorption (k~and the terminal phase of elimination (~) inversion of constants: k a <A 2 • Usage of A 2 , for the intravenous experiment, for the extrapolation of AUC po ' as AUC po n_~=Cn/ A 2 , underestimates AUC po n-~because absorption is not terminated at tn=24 h after p.o.…”
Section: Resultssupporting
confidence: 78%
“…Verapamil exhibits bi-or triphasic elimination kinetics and is reported to have a terminal plasma half-life of 2 to 8 hours following a single oral (non-retard) dose or after intravenous administration (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). There is considerable interindividual variation reported in plasma concentrations, with peak plasma concentrations within 1 to 2 hours of oral administration.…”
Section: Please Sendreprint Requests To:jovan Popovicmentioning
confidence: 99%
“…It was reported that CYP3A4 was mainly responsible for the metabolism of verapamil in humans, whereas CYP3A1/2 govern the metabolism of verapamil in rats (Tracy et al, 1999;Choi and Burm, 2008;Hanada et al, 2008). Verapamil undergoes extensive first-pass metabolism, with low oral bioavailability (10 -20%) in various animal species (Schomerus et al, 1976;Woodcock et al, 1981). The hepatic extraction ratio of verapamil was calculated to be 0.437 in the study.…”
Section: Introductionmentioning
confidence: 99%
“…For the immediate release formulation, studies have shown that more than 90% of the orally administered dose of verapamil is absorbed. Because of the rapid biotransformation of verapamil during its first pass through the portal circulation, its bioavailability ranges from 20% to 35% (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The bioavailability of verapamil for the sustained release formulations has been found to be similar to that of the immediate release preparations, although the rates of absorption are of course, different (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 97%
“…Verapamil, a calcium-channel blocker and a class IV antiarrhythmic, is approximately 90% absorbed from the GI tract, but is subject to very considerable first-pass metabolism in the liver and its bio-availability is only about 20-35% (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). It is metabolized in the liver into at least 12 metabolites, of which norveraparnil has been shown to have some activity.…”
Section: Introductionmentioning
confidence: 99%